PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA KLINIK BUNDA MULYA PARUNG PANJANG - Dwiki Imam Alpian; Aldila Rahma Putri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The purpose of this study is to determine the Influence of Service Quality and Location on Customer Satisfaction. The research method used is a quantitative descriptive method. The sampling technique used the Slovin formula, so that a sample of 94 respondents was obtained. Meanwhile, the primary data collection technique is through a questionnaire which is processed using the SPSS Application System Version 25. The data analysis method uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of this study are that the quality of service has a positive and significant effect on Customer Satisfaction with a value with a determination coefficient value of 72.3%, a hypothesis test of a t-count > t table or 3.221 > t a table of 1,662 or a significance of 0.000 < 0.05. location has a positive and significant effect on Customer Satisfaction with a determination coefficient value of 83.7% and a hypothesis obtained t count: 1.948 > t table: 1.662 or a significance of 0.000 < 0.05. The effect of service quality and location simultaneously had a positive and significant effect on customer satisfaction with the regression equation Y = 1,304 + 0.206X1 + 0.770X2. The value of the determination coefficient is 84.7%, The hypothesis test obtained a value of F calculated: 251,963 > F table: 2.705, Keywords: Customer Quality, Customer Satisfaction, Coefficient of Determination, Simultaneous